Photoswitchable vesicles - Basílio, Nuno; García-Río, Luis (Current opinion in colloid & interface science, 2017)
Vesicles are self-assembled nanosized structures that result from the auto-organization of amphiphilic compounds into closed bilayers. These systems are highly attractive subjects of fundamental research owing to their role as biomimetic models of cell membranes and compartmentalization systems. Vesicles also display very interesting features and properties for practical applications, namely as superior nanocontainers for encapsulation of functional molecules and materials. Exerting control over the formation, dissociation and permeability of these containers is therefore of paramount importance for many of their potentials applications. Being light the stimulus of choice for remote spatiotemporal control, we have compiled and revised selected published works on photoresponsive vesicles with the aim of providing an overview of the main strategies, advantages and limitations of such systems. [Display omitted]